Making Renaissance art - Woods, Kim W. (Renaissance art reconsidered, 2007)
Drawing and workshop practices / Catherine King -- Constructing space in Renaissance painting / Carol M. Richardson -- The illusion of life in fifteenth-century sculpture / Kim W. Woods -- Architecture: theory and practice / Tim Benton -- Making Renaissance altarpieces / Diana Norman -- The printed picture in the Renaissance / Charles Harrison -- Making histories, publishing theories / Catherine King